Adaptive image watermarking using bidimensional empirical mode decomposition - Mohammed Arrazaki; Abdelouahed Sabri; Mohamed Zohry; Tarek Zougari (Institute of Advanced Engineering and Science, 2023)
Digital watermarking is considered one of the technological means used to guarantee the security and authenticity of data transmitted over communication systems. A new method of image watermarking using the bidimensional empirical mode decomposition (BEMD) will be presented in this article, where the new idea is to use the BEMD of both the cover image and the watermark image. The embedding process consists of adding to each intrinsic modal function (IMF) of the cover image the corresponding IMF of the watermark image. The watermarked image contains three different watermarks and appropriate frequencies, which makes it more robust. We use this method for two reasons: first, to conserve the constituent characteristics of each IMF and second, to ensure the invisibility of the watermark. The results obtained showed a good response against different kinds of attacks. This technique has been compared with other methods of image watermarking based on decomposition BEMD, which showed good results.